Economic Evaluation of the National Program for Community Empowerment on Indonesian Rural Poverty: A Case Study of Aceh Province - Oktarina, Sachnaz Desta; Furuy, Jun (European Journal of Sustainable Development, 2016)
As the largest community-driven development (CDD) program in the globe, National Program for Community Empowerment of Indonesia (PNPM Mandiri) faces a noble target to achieve Sustainable Development Goal (SDG) which is declared in 2015 that formerly named Millennium Development Goal (MDG). In the intervening time, PNPM Mandiri is transformed to newly-established institution, Village Law, according to the Law no.6 / 2014. For encountering those challenges policy-makers needs to evaluate their existed development program and re-design the blueprint of present institution to favor the marginalized poor to sustain their economic viability. This article seeks to investigate determinants of village budget allocation of PNPM Mandiri investments from its first earmarked in 2007 and 2011. An evaluation of their return to investment in terms of poverty mitigation within the time frame was also incorporated within the study. It was finally documented that villages-specific endowment prior to PNPM Mandiri establishment were suggested to have reasonable contribution to endogeneity on villagers’ decision to select particular allocations. And the allocation of investment were relatively significant to alleviate village’s poverty. Keywords: Community-Driven Development Program, Budget Allocation, Poverty, Economic Evaluation